Gene therapy targeting cord blood-derived CD34+ cells from HIV-exposed infants: preclinical studies - Li, Xinqiang; Gervaix, A.; Kang, D.; Law, P.; Spector, S. A.; Ho, Anthony Dick; Wong-Staal, F. (Gene therapy, 1998)
Hematopoietic CD34+ cells from placental and umbilical cord blood (PUCB) can be valuable vehicles for gene therapy of immunodeficiencies and genetic disorders. We have conducted preclinical studies towards the treatment of HIV-1-infected infants with genetically ‘immunized’ CD34+ cells derived from PUCB using anti-HIV-1 hairpin ribozyme genes. PUCB was collected from 10 newborns of HIV-1-positive mothers. CD34+ cells were enriched with a modified procedure using Dynal immunomagnetic beads and chymopapain, stimulated with stem cell factor (SCF), IL-3 and IL-6, and transduced using cell-free recombinant retroviral vector (MJT) expressing a ribozyme against the U5 region of HIV-1. No significant differences were observed in the growth pattern of CD34+ cells from normal infants, HIV-1 exposed infants or infants confirmed to be infected by HIV-1. The transduction efficiency of the CD34+ cells from all the infants was also comparable. MJT-transduced CD34+ cells from an HIV-1-infected infant were maintained in a liquid culture system for 4 weeks, and the progeny macrophage cells were challenged with the monocyte-tropic laboratory strain, HIV-Bal, or the HIV-1 isolate from the infant’s mother. Significant inhibition of virus replication was observed in ribozyme-transduced cells. Thus, we have demonstrated efficient and stable gene transfer into progenitor cells from the cord blood of HIV-1-exposed or -infected infants and shown that protection from HIV-1 infection was conferred to the progeny cells produced by CD34+ cells transduced with the anti-HIV ribozyme gene construct.
Im Titel ist das Pluszeichen hochgestellt
Gesehen am 30.10.2025